Modified microcapsule-based recycled concrete with self-repairing function and preparation method thereof

By using modified microcapsules in recycled concrete and adopting the "triple-repair mechanism", the problems of microcapsules in recycled concrete are solved, and the overall performance of recycled concrete is significantly improved. and durability.

CN119462016APending Publication Date: 2025-02-18CHINA MCC5 GROUP CORP LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411650483.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The shell strength of microcapsules in existing recycled concrete is not suitable, the interface bonding performance is poor, and the dispersion is poor, resulting in uneven repair effect, poor storage stability, short effective period, and difficult to accurately control the amount of repair agents.

Method used

Modified microcapsules are used, and the capsule wall modified material is composed of bisphenol A type epoxy resin, silane coupling agent, nano SiO2 and γ-aminopropyl triethoxysilane, etc. The capsule core modified material is composed of modified amines It consists of curing agents, expanded montmorillonite, nano CaCO3 and thixotropic agents, and realizes the "triple repair mechanism" through intelligent triggering mechanism, active penetration repair and synergistic enhancement.

Benefits of technology

The compatibility and dispersion of microcapsules and recycled concrete substrates are improved, the preparation process is optimized, and the overall performance and durability of recycled concrete are significantly improved, achieving the coordinated repair of "new and old cracks".

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of recycled concrete, and particularly relates to recycled concrete with a self-repairing function based on modified microcapsules and a preparation method of the recycled concrete. The recycled concrete is prepared from the following raw materials in parts by weight: 400 + / -20 parts of cement, 780 + / -30 parts of recycled coarse aggregate, 680 + / -30 parts of recycled fine aggregate, 180 + / -10 parts of water, 20 + / -2 parts of modified microcapsules, 4.0 + / -0.2 parts of a water reducing agent and 0.4 + / -0.1 parts of an air entraining agent. The modified microcapsule self-repairing system disclosed by the invention has an intelligent triggering mechanism, active permeation repairing and synergistic enhancement effects. The multi-repairing mechanism is especially suitable for the recycled concrete and has the characteristics that newly generated interface cracks can be treated, original micro-cracks in the recycled aggregate can be repaired, and synergistic repairing of new and old cracks is achieved. Through accurate design of material components and optimization of process parameters, the repairing system can stably exist in a complex environment of the recycled concrete and effectively play a role, and the overall performance and durability of the recycled concrete are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of recycled concrete, and in particular relates to recycled concrete with self-repairing function based on modified microcapsules and a preparation method thereof. Background Art

[0002] Problems with traditional microcapsules in recycled concrete: 1) The shell strength is not suitable and breaks too early or too late; 2) Poor interface bonding with the recycled concrete matrix; 3) Poor dispersibility and easy agglomeration; 4) Poor storage stability and short shelf life; 5) The amount of repair agent is difficult to accurately control.

[0003] Unique challenges of recycled concrete: 1) The surface of recycled aggregate is rough, which can easily damage microcapsules; 2) The water absorption rate is high, which affects the water-cement ratio around the microcapsules; 3) The interface transition zone is complex, which affects the repair effect.

[0004] Because recycled concrete uses recycled aggregate, its internal structure is more complex than that of ordinary concrete. There are "new and old interfaces" (the interface between new slurry and recycled aggregate, and the interface between original slurry and original aggregate in recycled aggregate), and the recycled aggregate itself has microcracks and defects. These characteristics make recycled concrete more prone to cracks, and the crack propagation path is more complicated. Existing self-repairing technologies are mainly designed for ordinary concrete, such as microbial methods, simple epoxy resin microcapsules, etc., which cannot adapt well to the special structure of recycled concrete.

[0005] In summary, the main disadvantages of the existing technology are: the strength of the microcapsule shell material does not match the stress of the recycled concrete cracks; the interface bonding performance is poor, which affects the repair effect; poor dispersibility leads to uneven repair; poor stability during storage and transportation; and complex preparation process and high cost. Summary of the invention

[0006] In order to solve the above-mentioned problems existing in the prior art, the purpose of the present invention is to provide a recycled concrete with self-repairing function based on modified microcapsules and a preparation method thereof, improve the compatibility of microcapsules with the recycled concrete matrix, improve the dispersibility and stability of microcapsules, optimize the preparation process and reduce costs.

[0007] The technical solution adopted by the present invention is:

[0008] A recycled concrete with self-repairing function based on modified microcapsules, comprising the following raw materials in parts by weight: 400±20 parts of cement, 780±30 parts of recycled coarse aggregate, 680±30 parts of recycled fine aggregate, 180±10 parts of water, 20±2 parts of modified microcapsules, 4.0±0.2 parts of water reducing agent, and 0.4±0.1 parts of air entraining agent;

[0009] The modified microcapsules are prepared from the following raw materials in parts by weight: capsule wall modification material: capsule core material = 1: (0.84-0.99);

[0010] The capsule wall modification material is prepared from the following raw materials in parts by weight: 100 parts of bisphenol A epoxy resin, 8-12 parts of silane coupling agent, 3-5 parts of nano-SiO2 material, 5-8 parts of gamma-aminopropyl triethoxysilane, and 2-4 parts of epoxy silane;

[0011] The capsule core modified material is prepared from the following raw materials in parts by weight: 47-53 parts of modified amine curing agent, 15-20 parts of expanded montmorillonite, 5-8 parts of nano-CaCO3 material, 4-7 parts of thixotropic agent, 4-7 parts of coupling agent and 2.8-4 parts of dispersant.

[0012] The modified microcapsule self-repairing system proposed in the present invention has a "triple repair mechanism":

[0013] 1) Intelligent trigger mechanism: The microcapsule wall is made of a special modified epoxy resin, which is modified by a silane coupling agent and an interfacial compatibilizer to make it more sensitive to the stress in the recycled concrete and to be able to break and release the repair agent in time when cracks initiate.

[0014] 2) Active penetration repair: The capsule core uses low-viscosity modified epoxy resin as the matrix, and adds a special thixotropic agent system to control its rheological properties, so that the repair agent can quickly penetrate into the original cracks and newly generated cracks in the recycled aggregate. The unique coupling agent combination ensures that the repair agent can form a good chemical bond with both the old cement paste and the new cement paste in the recycled aggregate.

[0015] 3) Synergistic reinforcement: The nano-CaCO3 and modified montmorillonite added to the capsule core can not only enhance the mechanical properties of the repair material, but also react deeply with cement hydration products through their unique layered structure and ion exchange capacity. The CSH gel and other hydration products produced by this reaction can fill finer cracks while providing additional strength.

[0016] This multiple repair mechanism is particularly suitable for the characteristics of recycled concrete: it can not only treat newly generated interface cracks, but also repair the original micro cracks in the recycled aggregate, realizing the coordinated repair of "new and old cracks". Through the precise design of material components and the optimization of process parameters, the repair system can stably exist and effectively play a role in the complex environment of recycled concrete, significantly improving the overall performance and durability of recycled concrete.

[0017] This innovative design concept and unique mechanism of action have broken through the bottleneck of the application of traditional self-repairing technology in recycled concrete and provided a new technical approach to improve the quality of recycled concrete.

[0018] As a preferred embodiment of the present invention, the modified amine curing agent comprises the following raw materials in parts by weight: 45-48 parts of modified aliphatic amine or 45-48 parts of epoxy modified amine curing agent or 45-48 parts of polypropylene glycol diamine curing agent, and 2-5 parts of imidazole accelerator.

[0019] As a preferred embodiment of the present invention, the thixotropic agent comprises the following raw materials in parts by weight: 2 to 3 parts of organic bentonite, 1 to 2 parts of fumed silica, and 1 to 2 parts of castor oil derivatives; the coupling agent comprises the following raw materials in parts by weight: 2 to 3 parts of titanate coupling agent, 1 to 2 parts of aluminate coupling agent, and 1 to 2 parts of silane coupling agent; the dispersant comprises the following raw materials in parts by weight: 1.5 to 2 parts of polycarboxylate dispersant, 0.8 to 1.2 parts of polymer polyether dispersant, and 0.5 to 0.8 parts of silicone dispersant.

[0020] A method for preparing recycled concrete with self-repairing function based on modified microcapsules comprises the following steps:

[0021] S1: Raw material processing: recycled aggregate pretreatment, cement treatment, water reducing agent and air entraining agent treatment, modified microcapsule preparation;

[0022] S2: Ingredients: 400±20 parts of cement, 780±30 parts of recycled coarse aggregate, 680±30 parts of recycled fine aggregate, 180±10 parts of water, 20±2 parts of modified microcapsules, 4.0±0.2 parts of water reducer, and 0.4±0.1 parts of air entraining agent;

[0023] S3: Mixing: dry mixing stage and wet mixing stage.

[0024] As a preferred embodiment of the present invention, in step S1:

[0025] Recycled aggregate pretreatment: crushing and classification: particle size 5-25mm; mud content: ≤1%; needle-like content: ≤10%; surface treatment: soak in alkaline solution for 2h; micro powder treatment: spraying of silane coupling agent KH-550;

[0026] Cement treatment: Strength grade: PO 42.5; Specific surface area: ≥350m 2 / kg; standard consistency water consumption: 24% to 26%; initial setting time: ≥45min; final setting time: ≤600min;

[0027] Additive treatment including water reducing agent and air entraining agent: water reduction rate: ≥25%; air content: 4.5±1.5%; water seepage rate: ≤3%.

[0028] As a preferred embodiment of the present invention, in step S1, the modified microcapsules are prepared as follows:

[0029] Preparation of capsule wall and capsule core: capsule wall modification material: capsule core material = 1: (0.84-0.99);

[0030] Emulsification process: temperature: 35±2℃; O / W ratio: 1:3; emulsifier: OP-10; stirring speed: 600-800rpm; time: 30-40min; pH value: 6.8-7.2;

[0031] Interfacial polymerization: temperature: 40±2°C; catalyst: diethylenetriamine; curing temperature: 45±2°C; time: 2-3h; stirring speed: 300-400rpm;

[0032] Post-treatment: centrifugal separation: 2000rpm, 10min; washing times: 3 to 4 times; drying temperature: 45±2℃; drying time: 8 to 12h; screening specification: 50 to 200μm.

[0033] As a preferred embodiment of the present invention, the preparation of the capsule wall modification material comprises the following steps:

[0034] Heat the epoxy resin to 45±2°C; add the silane coupling agent and stir at 300rpm for 30min; raise the temperature to 60±2°C and add nano-SiO2; ultrasonically disperse for 15min; add γ-aminopropyltriethoxysilane and epoxysilane, stir at 450rpm for 60min; and vacuum degassing for 20min.

[0035] As a preferred embodiment of the present invention, the preparation of the capsule wall modification material comprises the following steps:

[0036] Heat the curing agent to 40±2°C; add the modified montmorillonite and stir at 400 rpm for 45 min; ultrasonically treat the montmorillonite for 15 min; add other components and stir at 500 rpm for 30 min; and vacuum degassing for 15 min.

[0037] As a preferred embodiment of the present invention, in step S2, the following requirements are met after batching:

[0038] Water-cement ratio: 0.45~0.50; sand ratio: 35~38%; microcapsule dosage coefficient: 4%~5%; water reducing agent dosage coefficient: 0.8%~1.2%.

[0039] As a preferred embodiment of the present invention, step S3 is specifically as follows:

[0040] Dry mixing stage: first stir the recycled aggregate for 15 seconds; add cement and continue stirring for 30 seconds; check the uniformity of the aggregate;

[0041] Wet mixing stage: add 80% water and stir for 60 seconds; add water reducer and stir for 30 seconds; add microcapsules and stir slowly for 45 seconds; add remaining water and stir for 90 seconds; let stand for 30 seconds and finally mix for 30 seconds;

[0042] Mixing requirements: Mixer speed: 18~22r / min; Ambient temperature: 20±5℃; Material temperature: ≤30℃.

[0043] The beneficial effects of the present invention are:

[0044] 1. Intelligent trigger mechanism: The microcapsule wall is made of special modified epoxy resin, which is modified by silane coupling agent and interfacial compatibilizer to make it more sensitive to the stress in the recycled concrete and can break and release the repair agent in time when cracks initiate.

[0045] 2. Active penetration repair: The capsule core uses low-viscosity modified epoxy resin as the matrix, and adds a special thixotropic agent system to regulate its rheological properties, so that the repair agent can quickly penetrate into the original cracks and newly generated cracks in the recycled aggregate. The unique coupling agent combination ensures that the repair agent can form a good chemical bond with both the old cement paste and the new cement paste in the recycled aggregate.

[0046] 3. Synergistic reinforcement: The nano-CaCO3 and modified montmorillonite added to the capsule core can not only enhance the mechanical properties of the repair material, but also react deeply with cement hydration products through their unique layered structure and ion exchange capacity. The CSH gel and other hydration products produced by this reaction can fill finer cracks while providing additional strength.

[0047] 4. This multiple repair mechanism is particularly suitable for the characteristics of recycled concrete: it can not only treat newly generated interface cracks, but also repair the original micro cracks in the recycled aggregate, realizing the coordinated repair of "new and old cracks". Through the precise design of material components and the optimization of process parameters, the repair system can stably exist and effectively play a role in the complex environment of recycled concrete, significantly improving the overall performance and durability of recycled concrete. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention are clearly and completely described below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.

[0049] Therefore, the following detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0050] 1. Detailed technical scheme for preparation of modified microcapsules:

[0051] 1. Preparation of capsule wall modified materials:

[0052] Step 1: Modification of base resin:

[0053] (1) Raw material composition (parts by weight):

[0054] Bisphenol A epoxy resin: 100 parts;

[0055] Silane coupling agent (KH-550, KH-570): 8-12 parts;

[0056] Nano-SiO2 (particle size 20-30nm, surface modified): 3-5 parts;

[0057] γ-aminopropyltriethoxysilane: 5-8 parts;

[0058] Epoxysilane: 2 to 4 parts.

[0059] (2) Preparation process parameters:

[0060] Heat the epoxy resin to 45±2°C; add silane coupling agent and stir at 300rpm for 30min; raise the temperature to 60±2°C and add nano-SiO2; ultrasonically disperse (power 400W) for 15min; add other modifiers (γ-aminopropyltriethoxysilane, epoxysilane), stir at 450rpm for 60min; vacuum degassing (-0.08MPa) for 20min.

[0061] 2. Preparation of capsule core material:

[0062] Step 1: Preparation of curing agent system:

[0063] (1) Raw material composition (parts by weight):

[0064] Modified amine curing agent: modified aliphatic amine (650 series): 45-48 parts, or epoxy modified amine curing agent (T31): 45-48 parts, or polypropylene glycol diamine curing agent (D230): 45-48 parts; imidazole accelerator (EMI-24): 2-5 parts;

[0065] Expandable montmorillonite (Na type, CEC ≥ 80mmol / 100g): 15-20 parts;

[0066] Nano-CaCO3 (particle size 50-70nm, surface modified): 5-8 parts;

[0067] Thixotropic agent: organic bentonite (BT-8): 2-3 parts, fumed silica (R972): 1-2 parts, castor oil derivative: 1-2 parts;

[0068] Coupling agent: titanate coupling agent (TC-100): 2-3 parts, aluminate coupling agent (AL-100): 1-2 parts, silane coupling agent (KH-560): 1-2 parts;

[0069] Dispersant: polycarboxylate dispersant (TLS-10): 1.5-2 parts, high molecular weight polyether dispersant (DJ-2030): 0.8-1.2 parts, silicone dispersant (BYK-377): 0.5-0.8 parts.

[0070] (2) Preparation process:

[0071] Heat the curing agent to 40±2°C; add the modified montmorillonite and stir at 400 rpm for 45 min; ultrasonically treat the montmorillonite for 15 min; add other components and stir at 500 rpm for 30 min; vacuum degassing (-0.06 MPa) for 15 min.

[0072] 3. Preparation of microcapsules:

[0073] Step 1: Emulsification process:

[0074] (1) Emulsification conditions: temperature: 35±2°C, O / W ratio: 1:3, emulsifier: OP-10 (3 wt% of the oil phase), stirring speed: 600-800 rpm, time: 30-40 min, pH value: 6.8-7.2.

[0075] Step 2: Interface polymerization:

[0076] Reaction conditions:

[0077] Temperature: 40±2°C; Catalyst: diethylenetriamine (1% of the resin mass); Curing temperature: 45±2°C; Time: 2-3h; Stirring speed: 300-400rpm.

[0078] Step 3: Post-processing:

[0079] Centrifugal separation: 2000rpm, 10min; washing times: 3 to 4 times; drying temperature: 45±2℃; drying time: 8 to 12h; screening specification: 50 to 200μm.

[0080] 2. Detailed technical scheme for the preparation of recycled concrete:

[0081] 1. Raw material requirements:

[0082] (1) Recycled aggregate pretreatment:

[0083] Crushing and classification: particle size 5-25mm; mud content: ≤1%; needle-like content: ≤10%; surface treatment: soak in alkaline solution (2% NaOH) for 2h; micro powder treatment: spray with silane coupling agent KH-550.

[0084] (2) Cement requirements:

[0085] Strength grade: PO 42.5; Specific surface area: ≥350m 2 / kg standard consistency water consumption: 24% ~ 26%; initial setting time: ≥45min; final setting time: ≤600min

[0086] (3) Requirements for admixtures:

[0087] Water reduction rate: ≥25%; air content: 4.5±1.5%; water seepage rate: ≤3%.

[0088] 2. Mix ratio design (kg / m 3 ):

[0089] (1) Basic mix ratio:

[0090] Cement: 400±20 parts; recycled coarse aggregate: 780±30 parts; recycled fine aggregate: 680±30 parts; water: 180±10 parts; modified microcapsules: 20±2 parts; water reducer: 4.0±0.2 parts; air entraining agent: 0.4±0.1 parts.

[0091] (2) Mix ratio adjustment coefficient:

[0092] Water-cement ratio: 0.45~0.50; sand ratio: 35%~38%; microcapsule dosage coefficient: 4%~5%; water reducing agent dosage coefficient: 0.8%~1.2%.

[0093] 3. Mixing process:

[0094] (1) Dry mixing stage:

[0095] First, stir the recycled aggregate for 15 seconds; add cement and continue stirring for 30 seconds; check the uniformity of the aggregate.

[0096] (2) Wet mix stage:

[0097] Add 80% of the water and stir for 60 seconds; add the water reducer and stir for 30 seconds; add the microcapsules and stir slowly for 45 seconds; add the remaining water and stir for 90 seconds; let it stand for 30 seconds and finally stir for 30 seconds.

[0098] (3) Mixing requirements:

[0099] Mixer speed: 18~22r / min; Ambient temperature: 20±5℃; Material temperature: ≤30℃.

[0100] 3. Self-repair performance:

[0101] Micro crack repair width: 0.1~0.8mm; repair depth: ≥2.5mm; 28-day repair rate: ≥90%; repair strength ratio: ≥85%; repair time: 7~14 days.

[0102] Detailed chemical reaction process of self-healing mechanism:

[0103] 1. Microcapsule rupture and repair agent release:

[0104] Crack stress triggers → modified epoxy resin microcapsules rupture → release of low viscosity epoxy matrix + nano-CaCO3 + modified montmorillonite.

[0105] 2. Main chemical repair reactions:

[0106] (1) Ring-opening reaction of epoxy group.

[0107] (2) Silane coupling interface reaction:

[0108] R-Si(OC2H5)3+3H2O→R-Si(OH)3+3C2H5OH;

[0109] R-Si(OH)3+HO-matrix→R-Si-O-matrix+H2O.

[0110] (3) Nanomaterials enhance reactions:

[0111] Ca 2+ +2OH - +CO2→CaCO3↓+H2O; nano-CaCO3 catalyzes the formation of new calcium carbonate crystals.

[0112] 3. Synergistic repair effect:

[0113] (1) Montmorillonite interlayer intercalation reaction:

[0114] [Si-O]-[Al-O]+nH2O→[Si-O]-[H2O]n-[Al-O]; layered structure expansion, physical filling effect.

[0115] (2) CSH gel formation:

[0116] 3CaO·SiO2+(3-x+n)H2O→(CaO)x·SiO2·(H2O)n+(3-x)Ca(OH)2; the hydration products enhance the interfacial bonding.

[0117] There are three key stages in the repair mechanism:

[0118] 1. Intelligent triggering stage:

[0119] The crack stress reaches the critical strength of the microcapsule wall (0.8-1.2 MPa);

[0120] Modified epoxy resin wall material breaks quickly;

[0121] The repair agent is released in a targeted manner to the crack area.

[0122] 2. Active penetration stage:

[0123] Low viscosity system quickly fills cracks (penetration rate> 0.5mm / s);

[0124] Directed migration of nanomaterials;

[0125] Forming a continuous repair network.

[0126] 3. Strengthening and curing stage:

[0127] The epoxy group reacts quickly with the curing agent (curing time 12 to 24 hours);

[0128] Nanomaterials catalyze the formation of new crystals;

[0129] CSH gel network growth and strengthening.

[0130] The salient features of this multiple repair mechanism are:

[0131] 1. Strong targeting:

[0132] Special structures specially adapted to recycled concrete;

[0133] It can handle both new and old cracks at the same time.

[0134] 2. High repair efficiency:

[0135] Fast response (initial repair takes 3 to 6 hours);

[0136] The penetration depth is large (up to 2.5mm or more).

[0137] 3. Good durability:

[0138] Formation of chemical bonds;

[0139] It has a microscopic enhancement effect.

[0140] Example:

[0141] Basic formula A (quick repair type, 3 to 5 days) (parts by weight):

[0142] (1) Cyst wall material:

[0143] Bisphenol A type epoxy resin (E-51): 100 parts; polyetheramine D-400: 20 parts; KH-550: 8 parts; KH-570: 2.5 parts; nano-SiO2 (20nm): 4 parts; γ-aminopropyltriethoxysilane: 3 parts; epoxysilane: 2.5 parts.

[0144] (2) Core material: fast-acting amine curing agent: 50 parts; epoxy-modified amine curing agent (T31): 45 parts; imidazole accelerator (EMI-24): 5 parts; expanded montmorillonite: 15 parts; nano-CaCO3: 6 parts; TC-100: 2.5 parts; TLS-10: 1.8 parts; fumed silica (R972): 1 part.

[0145] Basic formula B (mid-term repair type, 7 to 10 days) (parts by weight):

[0146] Same as formula A, but the curing system is changed to: medium-speed amine curing agent: 50 parts; modified aliphatic amine (650 series): 47 parts; imidazole accelerator (EMI-24): 3 parts; other components remain unchanged.

[0147] Basic formula C (sustained-release repair type, 12-15 days) (parts by weight):

[0148] Same as formula A, but the curing system is changed to: slow amine curing agent (D230): 50 parts; polypropylene glycol diamine curing agent (D230): 48 parts; imidazole accelerator (EMI-24): 2 parts; other components remain unchanged.

[0149] Microencapsulation solution:

[0150] Solution 1 (quick fix):

[0151] A:B:C=8:2:0.

[0152] Repair characteristics: initial repair rate (3 days): 65%; complete repair time: 5 days; repair strength recovery rate: 85%.

[0153] Solution 2 (standard repair):

[0154] A:B:C=5:4:1.

[0155] Repair characteristics: initial repair rate (3 days): 45%; complete repair time: 8 days; repair strength recovery rate: 92%.

[0156] Solution 3 (continuous repair):

[0157] A:B:C=2:3:5.

[0158] Repair characteristics: initial repair rate (3 days): 25%; complete repair time: 15 days; repair strength recovery rate: 95%.

[0159] Recycled concrete mix ratio (kg / m 3 ):

[0160] Quick repair type: cement (PO 42.5): 400 parts; recycled coarse aggregate: 780 parts; recycled fine aggregate: 680 parts; water: 180 parts; modified microcapsule (Scheme 1): 20 parts; water reducer: 4.0 parts; air entraining agent: 0.4 parts.

[0161] Standard repair type: cement (PO 42.5): 400 parts; recycled coarse aggregate: 780 parts; recycled fine aggregate: 680 parts; water: 180 parts; modified microcapsule (Scheme 2): 20 parts; water reducer: 4.0 parts; air entraining agent: 0.4 parts.

[0162] Continuous repair type: cement (PO 42.5): 400 parts; recycled coarse aggregate: 780 parts; recycled fine aggregate: 680 parts; water: 180 parts; modified microcapsule (Scheme 3): 20 parts; water reducer: 4.0 parts; air entraining agent: 0.4 parts.

[0163] Comparison of performance indicators of recycled concrete:

[0164] (1) Mechanical properties:

[0165] 28d compressive strength: 44-46MPa (difference among various schemes <5%); 28d flexural strength: 4.8-5.2Mpa; elastic modulus: 28-30Gpa.

[0166] (2) Repair performance:

[0167] Quick repair type: 3d repair rate: 65%; 5d repair rate: 85%; 7d repair rate: 90%.

[0168] Standard repair type: 3d repair rate: 45%; 5d repair rate: 70%; 8d repair rate: 92%.

[0169] Continuous repair type: 3d repair rate: 25%; 7d repair rate: 60%; 15d repair rate: 95%.

[0170] (3) Durability index:

[0171] Anti-seepage grade: P8; Anti-freeze grade: F150; Chloride ion diffusion coefficient: 2.3×10 -12 m 2 / s;

[0172] Repair rate test calculation method:

[0173] 1. Repair rate test:

[0174] (1) Specimen preparation: Prepare standard specimens (100 mm × 100 mm × 400 mm); standard curing for 28 days; the number of specimens in each group shall not be less than 6.

[0175] (2) Prefabricated cracks: three-point bending loading was used; the loading speed was controlled at 0.05 mm / min; the target crack width was generated at 0.1 to 0.3 mm; the initial crack parameters were recorded: crack width (W0), crack length (L0), and crack depth (D0).

[0176] (3) Repair and maintenance:

[0177] Temperature: 20±2℃; Relative humidity: 95%±5%; Curing time: n days.

[0178] 2. Calculation of repair rate:

[0179] (1) Width repair rate (WR): WR = (W0-Wn) / W0×100%.

[0180] Where: W0 = initial crack width; Wn = crack width after n days.

[0181] (2) Depth repair rate (DR): DR = (D0-Dn) / D0×100%.

[0182] Where: D0 = initial crack depth; Dn = crack depth after n days.

[0183] (3) Strength recovery rate (SR): SR = (Fn-Fd) / (F0-Fd) × 100%.

[0184] Where: F0 = initial flexural strength; Fd = strength after cracks occur; Fn = strength after repair n days.

[0185] (4) Permeability improvement rate (PR): PR = (P0-Pn) / P0 x 100%.

[0186] Where: P0 = initial water seepage; Pn = water seepage after n days of repair.

[0187] 3. Calculation of comprehensive repair rate:

[0188] The repair rate in n days = α×WR+β×DR+γ×SR+δ×PR.

[0189] Recommended values ​​of weight coefficients: α=0.3 (width repair weight); β=0.2 (depth repair weight); γ=0.3 (strength recovery weight); δ=0.2 (permeability improvement weight).

[0190] 4. Specific test steps:

[0191] (1) Crack width measurement: Use a digital microscope (50-200 times); measure one point every 10 mm along the crack; measure no less than 10 points for each crack; remove outliers and take the average value.

[0192] (2) Crack depth measurement: ultrasonic method; measurement point spacing: 10 mm; no less than 5 points for each crack; average value for calculation.

[0193] (3) Strength test: four-point bending test; loading rate: 0.05 mm / min; record the maximum load; calculate the flexural strength.

[0194] (4) Permeability test: use water seepage test method; water pressure: 0.1Mpa; test time: 1h; record the amount of water seepage.

[0195] Because recycled concrete uses recycled aggregate, its internal structure is more complex than that of ordinary concrete. There are "new and old interfaces" (the interface between new slurry and recycled aggregate, and the interface between original slurry and original aggregate in recycled aggregate), and the recycled aggregate itself has microcracks and defects. These characteristics make recycled concrete more prone to cracks, and the crack propagation path is more complicated. Existing self-repairing technologies are mainly designed for ordinary concrete, such as microbial methods, simple epoxy resin microcapsules, etc., which cannot adapt well to the special structure of recycled concrete.

[0196] The modified microcapsule self-repairing system proposed in the present invention has a "triple repair mechanism":

[0197] Intelligent trigger mechanism:

[0198] The microcapsule wall is made of a special modified epoxy resin, which is modified by a silane coupling agent and an interfacial compatibilizer to make it more sensitive to the stress in the recycled concrete and to break and release the repair agent in time when cracks initiate.

[0199] Active penetration repair:

[0200] The capsule core uses low-viscosity modified epoxy resin as the matrix, and adds a thixotropic agent system to regulate its rheological properties, so that the repair agent can quickly penetrate into the original cracks and newly generated cracks in the recycled aggregate.

[0201] The coupling agent combination ensures that the repair agent can form good chemical bonds with both the old and new cement pastes in the recycled aggregate.

[0202] Synergistic effect:

[0203] The nano-CaCO3 and modified montmorillonite added to the capsule core can not only enhance the mechanical properties of the repair material, but also react deeply with cement hydration products through their unique layered structure and ion exchange capacity.

[0204] The CSH gel and other hydration products produced by this reaction are able to fill finer cracks while providing additional strength.

[0205] This multiple repair mechanism is particularly suitable for the characteristics of recycled concrete: it can not only treat newly generated interface cracks, but also repair the original micro cracks in the recycled aggregate, realizing the coordinated repair of "new and old cracks". Through the precise design of material components and the optimization of process parameters, the repair system can stably exist and effectively play a role in the complex environment of recycled concrete, significantly improving the overall performance and durability of recycled concrete.

[0206] This innovative design concept and unique mechanism of action have broken through the bottleneck of the application of traditional self-repairing technology in recycled concrete and provided a new technical approach to improve the quality of recycled concrete.

[0207] The present invention is not limited to the above-mentioned optional implementation modes. Anyone can derive other various forms of products under the inspiration of the present invention. However, no matter what changes are made in the shape or structure, all technical solutions that fall within the scope defined by the claims of the present invention fall within the protection scope of the present invention.

Claims

1. A recycled concrete with self-repairing function based on modified microcapsules, characterized in that: The raw materials include the following parts by weight: 400±20 parts of cement, 780±30 parts of recycled coarse aggregate, 680±30 parts of recycled fine aggregate, 180±10 parts of water, 20±2 parts of modified microcapsules, 4.0±0.2 parts of water reducing agent, and 0.4±0.1 parts of air entraining agent; The modified microcapsules are prepared from the following raw materials in parts by weight: capsule wall modification material: capsule core material = 1: (0.84-0.99); The capsule wall modification material is prepared from the following raw materials in parts by weight: 100 parts of bisphenol A epoxy resin, 8-12 parts of silane coupling agent, 3-5 parts of nano-SiO2 material, 5-8 parts of gamma-aminopropyl triethoxysilane, and 2-4 parts of epoxy silane; The capsule core modified material is prepared from the following raw materials in parts by weight: 47-53 parts of modified amine curing agent, 15-20 parts of expanded montmorillonite, 5-8 parts of nano-CaCO3 material, 4-7 parts of thixotropic agent, 4-7 parts of coupling agent and 2.8-4 parts of dispersant.

2. The recycled concrete with self-repairing function based on modified microcapsules according to claim 1, characterized in that: The modified amine curing agent comprises the following raw materials in parts by weight: 45-48 parts of modified aliphatic amine or 45-48 parts of epoxy modified amine curing agent or 45-48 parts of polypropylene glycol diamine curing agent, and 2-5 parts of imidazole accelerator.

3. The recycled concrete with self-repairing function based on modified microcapsules according to claim 1, characterized in that: The thixotropic agent comprises the following raw materials in parts by weight: 2 to 3 parts of organic bentonite, 1 to 2 parts of fumed silica, and 1 to 2 parts of castor oil derivatives; the coupling agent comprises the following raw materials in parts by weight: 2 to 3 parts of titanate coupling agent, 1 to 2 parts of aluminate coupling agent, and 1 to 2 parts of silane coupling agent; the dispersant comprises the following raw materials in parts by weight: 1.5 to 2 parts of polycarboxylate dispersant, 0.8 to 1.2 parts of polymer polyether dispersant, and 0.5 to 0.8 parts of silicone dispersant.

4. A method for preparing recycled concrete with self-repairing function based on modified microcapsules, used for preparing the recycled concrete with self-repairing function based on modified microcapsules according to claim 1, characterized in that: The following steps are involved: S1: Raw material processing: recycled aggregate pretreatment, cement treatment, water reducing agent and air entraining agent treatment, modified microcapsule preparation; S2: Ingredients: 400±20 parts of cement, 780±30 parts of recycled coarse aggregate, 680±30 parts of recycled fine aggregate, 180±10 parts of water, 20±2 parts of modified microcapsules, 4.0±0.2 parts of water reducer, and 0.4±0.1 parts of air entraining agent; S3: Mixing: dry mixing stage and wet mixing stage.

5. The method for preparing recycled concrete with self-repairing function based on modified microcapsules according to claim 4, characterized in that: In step S1: Recycled aggregate pretreatment: crushing and classification: particle size 5-25mm; mud content: ≤1%; needle-like content: ≤10%; surface treatment: soak in alkaline solution for 2h; micro powder treatment: spraying of silane coupling agent KH-550; Cement treatment: Strength grade: PO 42.5; Specific surface area: ≥350m 2 / kg; standard consistency water consumption: 24% to 26%; initial setting time: ≥45min; final setting time: ≤600min; Including water reducing agent and air entraining agent admixture treatment: water reduction rate: ≥25%; Gas content: 4.5±1.5%; Water seepage rate: ≤3%.

6. The method for preparing recycled concrete with self-repairing function based on modified microcapsules according to claim 4, characterized in that: In step S1, the modified microcapsules are prepared by: Preparation of capsule wall and capsule core: capsule wall modification material: capsule core material = 1: (0.84-0.99); Emulsification process: temperature: 35±2℃; O / W ratio: 1:3; emulsifier: OP-10; stirring speed: 600~800rpm; time: 30~40min; pH value: 6.8-7.2; Interfacial polymerization: temperature: 40±2°C; catalyst: diethylenetriamine; curing temperature: 45±2°C; time: 2-3h; stirring speed: 300-400rpm; Post-treatment: centrifugal separation: 2000rpm, 10min; washing times: 3 to 4 times; drying temperature: 45±2℃; drying time: 8 to 12h; screening specification: 50 to 200μm.

7. The method for preparing recycled concrete with self-repairing function based on modified microcapsules according to claim 6, characterized in that: The preparation of the capsule wall modification material comprises the following steps: Heat the epoxy resin to 45±2°C; add the silane coupling agent and stir at 300rpm for 30min; raise the temperature to 60±2°C and add nano-SiO2; ultrasonically disperse for 15min; add γ-aminopropyltriethoxysilane and epoxysilane, stir at 450rpm for 60min; and vacuum degassing for 20min.

8. The method for preparing recycled concrete with self-repairing function based on modified microcapsules according to claim 6, characterized in that: The preparation of the capsule wall modification material comprises the following steps: Heat the curing agent to 40±2°C; add the modified montmorillonite and stir at 400 rpm for 45 min; ultrasonically treat the montmorillonite for 15 min; add other components and stir at 500 rpm for 30 min; and vacuum degassing for 15 min.

9. The method for preparing recycled concrete with self-repairing function based on modified microcapsules according to claim 4, characterized in that: In step S2, the following requirements are met after batching: Water-cement ratio: 0.45~0.50; sand ratio: 35~38%; microcapsule dosage coefficient: 4%~5%; water reducing agent dosage coefficient: 0.8%~1.2%.

10. The method for preparing recycled concrete with self-repairing function based on modified microcapsules according to claim 4, characterized in that: Step S3 is specifically as follows: Dry mixing stage: first stir the recycled aggregate for 15 seconds; add cement and continue stirring for 30 seconds; check the uniformity of the aggregate; Wet mixing stage: add 80% water and stir for 60 seconds; add water reducer and stir for 30 seconds; add microcapsules and stir slowly for 45 seconds; Add the remaining water and stir for 90 seconds; let stand for 30 seconds and finally stir for 30 seconds; Mixing requirements: Mixer speed: 18~22r / min; Ambient temperature: 20±5℃; Material temperature: ≤30℃.

Citation Information

Cited By

  • High-strength gravel concrete and preparation method thereof

    CN120365014A